Evaluating the quality and coverage of post-abortion care in Zimbabwe: a cross-sectional study with a census of health facilities - Taylor Riley; Mugove G. Madziyire; Onikepe Owolabi; Elizabeth A. Sully; Tsungai Chipato (BMC, 2020)
Abstract Background An estimated 65,000 abortions occurred in Zimbabwe in 2016, and 40 % resulted in complications that required treatment. Quality post-abortion care (PAC) services are essential to treat abortion complications and prevent future unintended pregnancies, and there have been recent national efforts to improve PAC provision. This study evaluates two components of quality of care: structural quality, using PAC signal functions, a monitoring framework of key life-saving interventions that treat abortion complications; and process quality, which examines the standards of care provided to PAC patients. Methods We utilized a 2016 national census of health facilities in Zimbabwe with PAC capacity (n = 227) and a prospective, facility-based 28-day survey of women seeking PAC in a nationally representative sample of those facilities (n = 1002 PAC patients at 127 facilities). PAC signal functions, which are the critical services in the management of abortion complications, were used to classify facilities as having the capability to provide basic or comprehensive care. All facilities were expected to provide basic care, and referral-level facilities were designed to provide comprehensive care. We also assessed population coverage of PAC services based on the WHO recommendation for obstetric services of 5 facilities per 500,000 residents. Results We found critical gaps in the availability of PAC services; only 21% of facilities had basic PAC capability and 10% of referral facilities had comprehensive capability. For process quality, only one-fourth (25%) of PAC patients were treated with the appropriate medical procedure. The health system had only 41% of the basic PAC facilities recommended for the needs of Zimbabwe's population, and 55% of the recommended comprehensive PAC facilities. Conclusion This is the first national assessment of the Zimbabwean health system's coverage and quality of PAC services. These findings highlight the large gaps in the availability and distribution of facilities with basic and comprehensive PAC capability. These structural gaps are a contributing barrier to the provision of evidence-based care. This study shows the need for increased focus and investment in expanding the provision of and improving the quality of these essential, life-saving PAC services.